Mobile SMS Categorization Using Rule Based Approach for Hindi and English Language - Anamika (My University, 2014)
Mobile Short Message Service (SMS) categorization is the method in which SMS is categorized in pre-defined categories. SMS has become the fastest way of communication. In SMS, a short text is sent to a person with whom one wants to chat. This is the easiest way to convey your message. By making excess use of SMS, a problem of overhead, in which messages got randomly stored in the Mobile phone's memory appears, so it becomes difficult to search out a particular message. For this problem, the TEXT CATEGORIZATION method is developed in which categorization of SMS is done in the predefined category like Greetings messages, Astrology messages, Health messages, shopping messages and so on. By using this categorization, it would become very easy to find out a particular message of particular category. This will save a lot of time which is very crucial to save in our hectic and busy lives. For text categorization, to categorize the SMS, there is a need to have a classifier which will classify all the text message into the predefined categories. For this purpose, it is very crucial to identify the classifiers very accurately. Those words whose appearance is unique in respect to all the text messages can be the classifiers for example if a word is appearing in many SMSs that means, that word is not unique so it will not be good decision to choose that word as a classifier.
ME, CSED
Keywords: stemmer; stop words; quantifier